2014
DOI: 10.5489/cuaj.1775
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo nephron-sparing surgery and autotransplantation for renal tumours: Revisited

Abstract: Introduction: We studied the feasibility of ex-vivo nephron-sparing surgery and autotransplantation for complex renal tumours. We also studied the role of laparoscopy in these situations. Methods: All patients who underwent renal autotransplantation for renal tumour at our centre were included in this retrospective study. Patient profiles were recorded in detail. Operative and postoperative details were also recorded. Results: Our series includes 3 patients. Two patients had complex renal cell carcinoma and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Previous reports have suggested LNA is an excellent long-term surgical option for complex ureteral pathology and severe renal disorder that necessitates preserving renal parenchyma. 2,7,10,14 To our knowledge this report represents the most robust data of the long-term safety, efficacy and durability of LNA. Our longterm (greater than 6-year median followup) experience validates the efficacy (greater than 90% preserved renal unit function) with acceptable (12%) late major complications.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous reports have suggested LNA is an excellent long-term surgical option for complex ureteral pathology and severe renal disorder that necessitates preserving renal parenchyma. 2,7,10,14 To our knowledge this report represents the most robust data of the long-term safety, efficacy and durability of LNA. Our longterm (greater than 6-year median followup) experience validates the efficacy (greater than 90% preserved renal unit function) with acceptable (12%) late major complications.…”
Section: Discussionmentioning
confidence: 81%
“…Other investigators have reported similar outcomes of LNA in experienced hands but these involve short-term followup and low patient numbers. 10,11 Five autotransplanted renal units failed, necessitating graft nephrectomy in 4, of which 2 were due to tumor progression. Of the 5 cases that required nephrectomy due to vascular complications 1 was due to chronic pain (ureteral stricture group) and 1 in the tumor group had local recurrence after nephron sparing surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables and (part‐a) summarize the key studies reporting the use of ReATx in oncological settings. The indications for ReATx included centrally located or multiple renal masses in the scenario of bilateral renal involvement or solitary functioning kidney . Primary urothelial carcinoma (UC) of the renal pelvis or the ureter in the setting of bilateral neoplastic involvement or solitary functioning kidney was also a common indication .…”
Section: Oncological Indications For Renal Autotransplantationmentioning
confidence: 99%
“…Renal autotransplantation (ReATx), despite having been reported as an effective treatment modality for managing complex renal/ureteral lesions , has remained underutilized. Two reasons may be cited for it—first, the high morbidity associated with the procedure due to the requirement for two major interventions, open nephrectomy and open transplantation, in the same setting.…”
Section: Introductionmentioning
confidence: 99%